Application of magnitude and phase angle to boundary area-based algorithm for unbalance relay protection scheme in 115-kV capacitor bank - Lertwanitrot, Praikanok; Ngaopitakku, Atthapol (IEEE access, 2021)
Identification of fault locations in capacitor banks is still under development. Although, faults in capacitor banks can be detected by an unbalance relay, it cannot identify the fault location. To address this issue, this study proposes an algorithm that can categorize protection zones, identify fault phases, and identify the fault locations in a capacitor bank using the phase angle boundary area. The result showed that the proposed algorithm was effective in indicating the fault location. Performance of the proposed algorithm was compared with conventional methods based on the Electricity Generating Authority of Thailand standard and phasor diagrams. It was verified that the proposed algorithm was more effective than the conventional methods. It is useful for the development of the unbalance relay operation.